- Optimization Of Digital Marketing Through A Search Engine Optimization (SEO) Approach In Indonesian Banking: - Yudanegara, Aditya; Saputera, Denny; Muttaqin, Rizqi (Journal of Business and Management Review, 2024)
Research Aims: The aim of this research is to explore the role and importance of Search Engine Optimization in the context of digital marketing and to analyze its implementation in the banking sector in Indonesia. This research aims to understand how SEO can improve visibility, credibility, and customer acquisition for banks and to provide insights into the factors that influence the effectiveness of SEO strategies in an ever-changing digital environment. Design/methodology/approach: The methodology in this research employs an exploratory qualitative approach. The data source consists of secondary data utilizing the SEO model on well-known banks in Indonesia. The analysis technique in this study utilizes the Miles & Huberman model, which involves the stages of Data Reduction, Data Display, and Conclusion Drawing or Verification.  Research Findings: focusing on SEO Bank Central Asia Tbk stands   out with a strong content strategy on Twitter, while Bank Mandiri Persero Tbk and Bank Rakyat Indonesia Persero Tbk prefer WhatsApp Web for direct customer communication. The use of WhatsApp Web by these banks demonstrates effectiveness in direct communication. Social traffic analysis also indicates differing strategies, with BCA focusing more on Twitter, while Bank Mandiri and BRI are more dominant on WhatsApp Web. Overall, the study shows that these banks have effectively adopted digital strategies, with SEO implementation successfully increasing their online visibility, expanding market reach, and strengthening brand image among consumers. Theoretical Contribution/Originality: This analysis provides deep insights into digital marketing strategies and the use of Search Engine Optimization (SEO) in the Indonesian banking sector. The findings offer a better understanding of the different approaches taken by leading banks such as BCA, Bank Mandiri, and BRI in leveraging online platforms to reach customers and expand their market reach. Theoretical implications of this analysis can provide a foundation for further research in the field of digital marketing and best practices in implementing SEO in the banking industry context. Keywords: Digital Marketing, Search Engine Optimization, Banking in Indonesia